Variations in running technique between female sprinters, middle, and distance runners - Cunningham, R.; Hunter, I.; Seeley, M. K.; Feland, B. (International Journal of Exercise Science, 2013)
In the sport of track and field, runners excel not only due to physiological characteristics but also aspects in running technique. Optimal technique allows runners the perfect the balance between running speed and economy. The ideal movement pattern may vary between events as the goal goes from economy of movement in the long-distance events to speed and power in the sprints. Understanding how each type of runner moves differently will help coaches more effectively train their athletes for each specific running event. This study was conducted to determine if sprinters, middledistance, and long-distance runners would exhibit differences in form while running at the same speeds. Thirty female Division I collegiate runners participated in this study. Runners were separated into categories based on the events for which they were currently training in: 10 sprinters, 10 middle-distance, and 10 long-distance runners. Participants were asked to run twenty-two steps at five selected speeds. Knee angles, ground contact time, center of mass separation, and stride length were measured using a Vicon Nexus motion analysis system. Data was processed using analysis of variance and a Tukey post hoc analysis. Significant differences (p < .05) occurred between long-distance runners and the other two groups (middle-distance and sprinters) for knee range, ground contact time, center of mass separation, and stride length at all five speeds. While running at the same speeds, there are specific characteristics of technique that distinguish long-distance runners from middle-distance and sprinters.